BWPA: Botswana Wildlife Producers Association - de Wet, Rudie, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Botswana is one of the success stories globally in terms of conservation. If you look at the ratios of land that is dedicated to conservation it ranks among the best in the world. We have a government which appreciates the value of conservation and the preservation of that. This effort also contributes to the popularity of Botswana's tourism sector as Botswana is rated as one of the best tourist destinations in the world. The game ranching industry in Botswana is relatively in its infant shoes as it started in the early 2000's. We have over a 100 registered game ranches with an average size of 9,000 hectares. The number of game animals on the ranches is currently a quarter of the total population of all Botswana's game numbers. Bearing in mind that the ranches cover 1% of Botswana's land mass and 8% of the combined areas including National Parks and Game Reserves. The ban of hunting had a huge effect on the game ranch industry as it is perceived globally that there is no hunting in Botswana, although it is permitted on registered game ranches. When hunting of big game was allowed in the concession areas we had a huge spin off from clients who wanted to hunt plains game on the ranches. It is currently very difficult to market Botswana as a hunting destination. The ban of hunting also had a huge effect on the communities who benefitted from that. I agree that it make sense to convert certain concession areas into photographic areas as it is ideally suited for that. But Botswana is a vast country and certain areas are not suited for photographic tourism. Hunting in those areas will ensure proper management where communities can benefit from it and also ensure survival of species as there will be proper anti-poaching measures put in place. There is also an increase in human animal conflict in Botswana after the ban of hunting where predators especially are affected. Botswana needs to relook at the ban to ensure a sustainable conservation effort.
The Botswana wildlife industry and consequences of ban on hunting
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.